4x+6=y-3

Simple and best practice solution for 4x+6=y-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+6=y-3 equation:


Simplifying
4x + 6 = y + -3

Reorder the terms:
6 + 4x = y + -3

Reorder the terms:
6 + 4x = -3 + y

Solving
6 + 4x = -3 + y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 4x = -3 + -6 + y

Combine like terms: 6 + -6 = 0
0 + 4x = -3 + -6 + y
4x = -3 + -6 + y

Combine like terms: -3 + -6 = -9
4x = -9 + y

Divide each side by '4'.
x = -2.25 + 0.25y

Simplifying
x = -2.25 + 0.25y

See similar equations:

| 8u+1=7u+1 | | 4k-2=k-6 | | 15+.25x= | | 3(2x+1)=5(x-4) | | 5(b-6)=3(b+4) | | x+y=4x | | 3(3-x)=15x-27 | | -5y+-5(6-2y)=0 | | 15x-10=-9x+3 | | lny=-3ln(x)+ln(C) | | 4-8x-x=-23 | | 3a^2+25a+50=0 | | 8q-5=5q+3 | | 2y+y-.5=23.5 | | 11-9=-23 | | X+6*4=126 | | 8x=4x-6 | | .4x^2+.2=x | | x-6-7=26(x-7) | | -8x-x=99 | | 6n+2=n+8 | | 2(9c-6)=14 | | -4m-2=82 | | -8(n-7)+3(n-3)=41 | | (9x+y)+(3x+2y)=180 | | -8(n-7)+3(n-3)=31 | | 64=8w-8 | | 2N+7(9N+10)= | | 6+.010x=0.15x+8 | | 4p+2=p+4 | | -5y-5(-62y)=0 | | 13.33+.11x=13.83+.08x |

Equations solver categories